PENINGKATAN INTERAKSI SOSIAL MELALUI PELATIHAN SABLON UNTUK ODMK DI KOMUNITAS GRIYA SCHIZOFREN, SURAKARTA - Triana Rahmawati; Ahmad Zuber; Theofilus Apolinaris Suryadinata; Aris Arif Mundayat; Rezza Dian Akbar; Fitri Ayu Handayani; Effieta Alfi Wulandari (Bajang Institute, 2026)
This community service program aims to improve social interaction of People with Mental Health Problems (ODMK) through sublimation screen printing training at the Griya Schizofren Community, Surakarta. Negative stigma towards ODMK causes social isolation and limited access to productive economy. The method used is participatory training with an inclusive approach involving 20 residents of Griya PMI. The results showed a significant increase in participants' social interactions, with more than 50% of residents showing improvements in communication and self-confidence. Participants were able to produce merchandise such as mugs, shirts, and tote bags marketed through the Solvenesia brand. This activity also succeeded in unraveling stigma through social media campaigns and collaboration with various parties. This program contributes to the achievement of SDGs points 3 (Good Health and Well-being), 4 (Quality Education), 8 (Decent Work and Economic Growth), and 10 (Reduced Inequalities). Program sustainability is supported by a funding system through dawn donations and happiness contributors.